DIVERSIFICATION OF DEVELOPMENT DEMOGRAPHIC CONDITIONS IN KOSZALIN AND OTHER SELECTED TOWNS (Research Bulletins of the Faculty of Economic Sciences, 2018)
Demographic processes are causing many consequences, which over time become increasingly clear. The main aim of the article was to assess diversification of development demographic conditions in Koszalin and other selected towns on the rights of the county in the northern or northwestern macroregion in 2010 and 2015. The research was done using the synthetic indicator. The analysis was based on twelve simply indicators characterizing the most important aspects of population processes, such as: natural increase, net migration and population structure. In most of the analysed towns changes in population process are rather negative. Particularly pessimistic is the natural increase and population structure are particularly pessimistic.
Keywords: demography, demographic conditions, towns